Needle fracture during local anesthesia: How to proceed? - Ferreira, Bruna Barcelos; Jorge Boos, Fernanda Brasil Daura [UNESP]; Stabile, Glaykon Alex Vitti (My University, 2015)
Fractures of gingival needles were relatively frequent in 60s, a period prior to the replacement of reusable needles and rigid by current disposable and flexible. These accidents are more prevalent during inferior alveolar nerve block in children. The conduct to be established will depend on several factors, including the patient's symptoms, position of the foreign body awkward and psychological aspects. The objective of this paper is to present the report of two clinical cases in which they were employed different forms of treatment and, through these, to guide the professional about how to proceed in this accident.